Implementation of Project-Based Learning Model in Stimulating Language Development of Early Childhood - Zatiah Lesyani; Erna Budiyarti; Nita Priyanti (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
This research is based on one of the current problems of early childhood education, namely the weakness of the learning process, which can facilitate all children in developing abilities and interests with varied, holistic, and conceptual learning models so that it can encourage children to develop the ability to think critically, creatively, independently and Motivated to complete every challenge. Educational institutions still use teacher-centered learning rather than children's needs, prioritizing memorization rather than needs and meaningfulness. Currently, it is mandatory for learning teachers to make learning activities more creative, innovative and not monotonous by using learning models that are more meaningful for children. Teachers can learn from various platforms provided by the government and can apply them according to the conditions of educators, children, and the institution itself. One of them uses a project-based learning model, where this learning model is one of the models used in the curriculum that facilitates children's needs so that children can learn in a fun and meaningful way, namely the Merdeka curriculum. The research aims to determine the implementation of the project-based learning model in stimulating language development in early childhood. The research subject focused on group A4 students at RA Istiqlal Jakarta. The data collection technique is qualitative descriptive with research time from September to December 2023. The research results show that the project-based learning model effectively stimulates children's development, including language development at RA Istiqlal Jakarta.